Moving beyond “the” business case: How to make corporate sustainability work - Busch, Timo; Barnett, Michael L.; Burritt, Roger Leonard; Cashore, Benjamin W.; Freeman, R. Edward; Henriques, Irene; Husted, Bryan W.; Panwar, Rajat; Pinkse, Jonatan; Schaltegger, Stefan; York, Jeff (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
One of the most investigated research topics in the corporate sustainability literature is “the” business case. Long lionized for linking the profit motive to corporate environmental initiatives, the business case for sustainability is now vehemently criticized. These critics generally argue for a return to the state and stronger regulatory frameworks. Others counter that because the private sector's capabilities are uniquely suited to realizing effective sustainability innovations and outcomes, we must not abandon but further develop our business case understanding. In this view, firms' voluntary efforts are key for innovative solutions to sustainability problems. This article overviews and unites these seemingly disparate positions. We move the field forward by placing in context criticisms and also opportunities for more meaningful positive impacts from corporate sustainability. Specifically, we argue that an effective business case orientation requires shifting to a broader “all stakeholders win” approach. This entails impact orientation, collaborative approaches, and economic restraint.
Keywords: Business Case; Grand Challenge; Net Present Value; Stakeholder Capitalism; Stakeholder